EFL Learners’ Engagement And Its Academic Effects In Shadow Education: Phenomenological Study - azizah, Nada; Nurkamto, Joko; Adi Putra, Kristian (CV. Inara, 2024)
In Indonesia, shadow education is becoming a promising educational business, which raises questions about the quality of the teaching at school and factors affecting such a phenomenon. The current phenomenological study aimed to find out kinds of engagement of ten Indonesian English as a Foreign Language (EFL) in Shadow Education (SE). It would also highlight academic effects of shadow education in Indonesia. Grounded in the interpretive paradigm, the study employed a qualitative approach to gain an in-depth and holistic picture of EFL learners’ lived experiences at shadow learning in Indonesia. Data were collected mainly through observation and interview. The data were analyzed by using coding and categorized into themes and categories in the meaning making and interpretation process. The study revealed that students were engaged beahiorally, emotionally and cognitively in SE. Dealing with the students' participation in SE, it was found that SE gave good effects for students' academics, such as giving satisfaction, helping them to understand English and prepare examination. Theoretically, study is expected to give understanding on how shadow education affects student engagement and its academic effects. Practically. This study informed teachers about good ELT practices in the SE to be adapted in their classroom .